Epimedium sagittatum inhibits TLR4/MD-2 mediated NF-κB signaling pathway with anti-inflammatory activity - Ni Yan; Ding-Sheng Wen; Yue-Rui Zhao; Shun-Jun Xu (BMC, 2018)
Abstract Background Epimedium sagittatum (Sieb.et Zucc.) Maxim., Ying-Yang-Huo in Chinese has been used as a traditional Chinese medicine and is deemed to "reinforce the kidney Yang". Previous studies showed that E. sagittatum could modulate the immune system and treat some chronic disease such as rheumatic arthritis, cardiovascular diseases and osteoporosis. The aim of this study is to evaluate the anti-inflammatory effects of ethyl acetate extracts (YYHs) of E. sagittatum and its mechanisms of action. Methods In order to explore the composition of YYHs, YYHs was analyzed using high performance liquid chromatography-mass spectrometry-mass spectrometry (HPLC-MS/MS) and in comparison with reference standards. Anti-inflammatory model was established in LPS-induced RAW264.7 cells. The levels of nitric oxide (NO) were measured with the Griess reagent. Production of tumor necrosis factor-alpha (TNF-α) and interleukin-2 (IL-2) were measured by enzyme-linked immunosorbent assays (ELISA). In addition, expression of p-p65 protein and TLR4/MD-2 complex was detected by western blots and flow cytometric, respectively. Nuclear factor kappa B (NF-κB) nuclear translocation was observed by fluorescence microscope. Results A total of eight compounds were identified, of which icariside II was the most abundant compound. YYHs (12.5-50 μg/mL) had no obvious cytotoxic effect on cells, and remarkably inhibited LPS-induced production of NO, TNF-α and IL-2 with a dose-dependent manner. Additionally, YYHs up-regulated expression of p-p65 and TLR4/MD-2 complex. Further research showed that YYHs significantly suppressed NF-κB p65 nuclear translocation. Conclusion In brief, YYHs contributed to the inhibition of LPS-induced inflammatory response through the TLR4/MD-2-mediated NF-κB pathway and may be a potential choice to combat inflammation diseases. Abstract graph It includes a schema of pathways at the end of the paper.